2014
DOI: 10.1200/jco.2013.54.0526
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific Immune Responses and Clinical Outcome After Vaccination With Glioma-Associated Antigen Peptides and Polyinosinic-Polycytidylic Acid Stabilized by Lysine and Carboxymethylcellulose in Children With Newly Diagnosed Malignant Brainstem and Nonbrainstem Gliomas

Abstract: A B S T R A C T PurposeDiffuse brainstem gliomas (BSGs) and other high-grade gliomas (HGGs) of childhood carry a dismal prognosis despite current treatments, and new therapies are needed. Having identified a series of glioma-associated antigens (GAAs) commonly overexpressed in pediatric gliomas, we initiated a pilot study of subcutaneous vaccinations with GAA epitope peptides in HLA-A2-positive children with newly diagnosed BSG and HGG. Patients and MethodsGAAs were EphA2, interleukin-13 receptor alpha 2 (IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
160
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(165 citation statements)
references
References 54 publications
1
160
3
1
Order By: Relevance
“…Extensive necrosis along with a small rim of viable tumor was noted at subsequent autopsy at many of the metastatic sites including the brain lesion [40]. Along the same lines, anecdotal reports highlight the occurrence of pseudoprogression among brain tumor patients treated with a variety of vaccine regimens [38,[41][42][43].…”
Section: Complexity Of Radiographic Worsening Following Immunotherapymentioning
confidence: 89%
“…Extensive necrosis along with a small rim of viable tumor was noted at subsequent autopsy at many of the metastatic sites including the brain lesion [40]. Along the same lines, anecdotal reports highlight the occurrence of pseudoprogression among brain tumor patients treated with a variety of vaccine regimens [38,[41][42][43].…”
Section: Complexity Of Radiographic Worsening Following Immunotherapymentioning
confidence: 89%
“…Inclusion in this trial required patients with HLA-A2-positive status and minimal or no dexamethasone usage at the time of enrollment. 86 In a separate Phase I trial of newly diagnosed patients with HGG between the ages of 1 and 18, autologous tumor lysate-pulsed DCs were generated for 3/ 9 enrolled patients with 2 of the DC-treated individuals still alive at 40 and 51 mo post-surgery, respectively. 87 Another Phase I trial using DCs treated with tumor lysate in 33 malignant glioma patients showed an average PFS of 19 weeks and OS of 59 weeks, with 7 patients surviving at the time of publication.…”
Section: Vaccines For Treatment Of Pediatric Malignant Gliomamentioning
confidence: 99%
“…A phase I study of a multi-epitope anti-survivin peptide vaccine (EMD640744) in patients with advanced solid tumors found an antigen-specific T-cell response in 63% of subjects, and 28% of vaccinated subjects achieved stable disease [Lennerz et al 2014]. Another phase I study in pediatric brainstem glioma patients using a tripeptide vaccine containing survivin and given in combination with the immunoadjuvant poly-ICLC (polyinosinicpolycytidylic acid stabilized by lysine and carboxymethylcellulose) showed evidence of survivinspecific immune responses and clinical benefit [Pollack et al 2014]. In grade 2 low-grade glioma patients, vaccination with survivin and three other glioma-associated peptides combined with poly-ICLC produced robust T H 1 immune responses [Okada et al 2015].…”
Section: Survivinmentioning
confidence: 99%